ICT AS EXPERIENTIAL TEACHING/LEARNING OPPORTUNITIES IN A PRIMARY SCHOOL: TEACHERS’ APPROACH - Šmitienė, Gražina; Braslauskiene, Rasa; Vismantiene, Reda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article reveals opportunities of information communication means in creating experiential teaching environments and provides insights for the development of experiential teaching/learning opportunities in a primary school. Experiential learning, which treats a person as a whole and emphasizes one’s unlimited potential opportunities, covers all three dimensions of teaching/learning: cognitive (i.e. perceptual), effective (emotional) and social (behavioural), and accordingly is a condition for the teaching/learning success. A qualitative research that involved teachers of primary schools (teachers of 1-2 and 3-4 grades) has been carried out. Content analysis of the results of the research revealed the essential conditions for using ICT means in creating experiential teaching/learning environments in a primary school and preconditions for creating experiential learning environments: sufficient special competences of primary school teachers to use ICT means, insufficient competences to create an experiential teaching/learning environment in a school (lack of knowledge and skills), lack of ICT means in classrooms, lack of cooperation between primary education teachers and of their motivation.